Empowered School Administration: The Effect of Structured Mentoring at An-Nur Kembang Jeruk Islamic School: Administrasi Sekolah Yang Berdaya: Efek Pendampingan Terstruktur Di Madrasah Diniyah An-Nur Kembang Jeruk - Khotibul Umam (Journal of Research and Community Service, 2024)
This research aims to examine the influence of structured mentoring on administrative empowerment at Madrasah Diniyah An-Nur, Kembang Jeruk. The primary focus of this research is to understand how a systematically designed mentoring process can improve the quality of administrative governance in community-based Islamic educational institutions. This research employs a descriptive qualitative approach with a case study as the research type. Data collection was conducted through in-depth interviews, participatory observation, and documentation, with the research units including the head of the madrasah, teachers, and administrative staff. Data were analyzed through the processes of reduction, presentation, and conclusion drawing, which were carried out continuously. The research results indicate that prior to the mentoring, the administration at Madrasah Diniyah An-Nur operated informally, was undocumented, and relied on oral habits and personal relationships. However, after the mentoring process, which included training, the development of a documentation system, as well as monitoring and evaluation, there was a significant improvement in aspects of letter documentation, activity planning, financial reporting, and internal coordination. The mentoring also triggered a transformation in work culture from individualistic to collaborative, and fostered the emergence of participatory leadership within the madrasah environment. The implications of this research underscore the importance of structured and sustainable administrative interventions in promoting the empowerment of local Islamic educational institutions.